Compound heterozygous PKHD1 variants cause a wide spectrum of ductal plate malformations. (8th September 2015) - Courcet, Jean‐Benoît; Minello, Anne; Prieur, Fabienne; Morisse, Laurent; Phelip, Jean‐Marc; Beurdeley, Alain; Meynard, Daniel; Massenet, Denis; Lacassin, Flore; Duffourd, Yannis; Gigot, Nadège; St‐Onge, Judith; et al.
Abstract : Ductal plate malformations (DPM) present with a wide phenotypic spectrum comprising Von Meyenburg complexes (VMC), Caroli disease (CD), Caroli syndrome (CS), and autosomal recessive polycystic kidney disease (ARPKD). Variants in PKHD1 are responsible for ARPKD and CS with a high inter‐ and intra‐familial phenotypic variability. Rare familial cases of CD had been reported and exceptional cases of CD are associated with PKHD1 variants. In a family of three siblings presenting with a wide spectrum of severity of DPM, we performed whole exome sequencing and identified two PKHD1 compound heterozygous variants (c.10444G>A; p.Arg3482Cys and c.5521C>T; p.Glu1841Lys), segregating with the symptoms. Two compound heterozygous PKHD1 variants, including one hypomorphic variant, were identified in two other familial cases of DPM with at least one patient presenting with CD. This report widens the phenotypic variability of PKHD1 variants to VMC, and others hepatic bile ducts malformations with inconstant renal phenotype in adults and highlights the important intra‐familial phenotypic variability. It also showed that PKHD1 might be a major gene for CD. This work adds an example of the contribution of exome sequencing, not only in the discovery of new genes but also in expanding the phenotypic spectrum of well‐known disease‐associated genes, using reverse phenotyping. © 2015 Wiley Periodicals, Inc.